Irony and misreading in the Annals of Tacitus - O'Gorman, Ellen (Cambridge University Press, 2000)
This book is a literary analysis of the language and style of Tacitus' Annals. The political context of first-second century AD Rome is also taken into consideration. Issues relating to the study of narrative, Roman politics and theories of history are addressed in the course of the discussion.